2021
DOI: 10.3389/fevo.2021.707570
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Ecosystem Linkages: Transfer of Polyunsaturated Fatty Acids From Streams to Riparian Spiders via Emergent Insects

Abstract: Polyunsaturated fatty acids (PUFAs) are essential resources unequally distributed throughout landscapes. Certain PUFAs, such as eicosapentaenoic acid (EPA), are common in aquatic but scarce in terrestrial ecosystems. In environments with low PUFA availability, meeting nutritional needs requires either adaptations in metabolism to PUFA-poor resources or selective foraging for PUFA-rich resources. Amphibiotic organisms that emerge from aquatic ecosystems represent important resources that can be exploited by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…Our finding that riparian and inland spider diets vary with distance from aquatic habitats generally echoes those of other recent studies on spider diets and PUFA sources at varying distances from streams (Chari et al, 2020;Kowarik et al, 2021) and lakes (Mathieu-Resuge et al, unpublished). Mathieu-Resuge et al (unpublished) reported that web-building spiders collected directly on emergence traps and those collected in terrestrial habitats at distances of 1-150 m from shore had different diet sources.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our finding that riparian and inland spider diets vary with distance from aquatic habitats generally echoes those of other recent studies on spider diets and PUFA sources at varying distances from streams (Chari et al, 2020;Kowarik et al, 2021) and lakes (Mathieu-Resuge et al, unpublished). Mathieu-Resuge et al (unpublished) reported that web-building spiders collected directly on emergence traps and those collected in terrestrial habitats at distances of 1-150 m from shore had different diet sources.…”
Section: Discussionsupporting
confidence: 90%
“…These ecosystem-based differences in fatty acid composition also persist at higher trophic levels: studies suggest that terrestrial insects contain little to no n-3 LC-PUFA, while emergent freshwater insects are rich in these compounds, especially EPA (Hixson et al, 2015;Martin-Creuzburg et al, 2017;Twining et al, 2019). Emergent aquatic insects from streams and lakes thus subsidize terrestrial predators not only with energy (e.g., Nakano and Murakami, 2001;Baxter et al, 2005;Kautza and Sullivan, 2016), but also with these physiologically important organic compounds (Martin-Creuzburg et al, 2017;Twining et al, 2019;Mathieu-Resuge et al, unpublished;Kowarik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations